A pulsed supersonic gas jet target for precision spectroscopy at the HITRAP facility at GSI - Tiedemann, Dirk; Stiebing, K. E.; Winters, D. F. A.; Quint, Wolfgang; Varentsov, V.; Warczak, A.; Malarz, A.; Stöhlker, Thomas (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
A pulsed supersonic gas jet target for experiments at the HITRAP facility at the GSI Helmholtzzentrum für Schwerionenforschung in Darmstadt has been designed and built as a multi-purpose installation for key experiments on fundamental atomic physics in strong fields. This setup is currently installed at the Institut für Kernphysik of Goethe-University, Frankfurt am Main (IKF), in order to explore its operation prior to its installation at the HITRAP facility. Design and performance of the target are described. The measured target densities of 5.9×1012atoms/cm3 for helium and 8.1×1012 atoms/cm³ for argon at the stagnation pressure of 30bar match the required values. The target-beam diameter of 0.9mm and the pulsed operation mode (jet built-up-time ≤15ms) are well suited for the use at HITRAP.